Anterior Knee Pain Evaluation Following Anterior Cruciate Ligament (ACL) Reconstruction Using Anterior Half of The Peroneus Longus (AHPL) Autograft - Pontoh LAP; Dilogo IH; Kamal AF; Rhatomy S; Putra A; Fiolin J; Herdiman JA; Pontoh EW (Orthopedic Research and Reviews, 2025)
Ludwig Andibert Powantia Pontoh,1,2 Ismail Hadisoebroto Dilogo,1 Achmad Fauzi Kamal,1 Sholahuddin Rhatomy,3 Anggaditya Putra,2 Jessica Fiolin,4 Joshua Alward Herdiman,5 Ega Wirayoda Pontoh5 1Department of Orthopaedic and Traumatology, Cipto Mangunkusumo General Hospital, Central Jakarta, DKI Jakarta, 10430, Indonesia; 2Department of Orthopaedic and Traumatology, Fatmawati General Hospital, South Jakarta, DKI Jakarta, 12430, Indonesia; 3Department of Orthopaedic and Traumatology, Soeradji Tirtonegoro General Hospital, Klaten, Central Java, 57424, Indonesia; 4Department of Orthopaedic and Traumatology, Pondok Indah General Hospital, South Jakarta, DKI Jakarta, 12310, Indonesia; 5Faculty of Medicine, Universitas Indonesia, Central Jakarta, DKI Jakarta, 10430, IndonesiaCorrespondence: Ludwig Andibert Powantia Pontoh, Email lappontoh@gmail.comIntroduction: The anterior cruciate ligament (ACL) is crucial for knee stability and joint movement coordination. ACL injuries are common, often leading to knee instability and subsequent complications. ACL reconstruction is a standard treatment option, with various autograft sources available. The anterior half of the peroneus longus (AHPL) tendon has emerged as a potential alternative autograft. This study aimes to examine the anterior knee pain in ACL reconstruction using AHPL.Materials and Methods: This study included 51 patients with ACL injuries undergoing ACL reconstruction using the AHPL tendon autograft. Patient demographics, surgical details, and Kujala scores were collected.Results: The average age of our participants was 25.88 ± 5.39 years, with mean BMI classified as obese. Significant improvements in Kujala and KOOS pain scores were observed between each data collection. There was a negative correlation between baseline and three and six months post-operatively Kujala and KOOS pain scores with BMI.Discussion: The study findings suggest that ACL reconstruction using the AHPL tendon autograft significantly reduced anterior knee pain, as indicated by a better Kujala and KOOS pain score. Previous studies have highlighted concerns regarding anterior knee pain with other autograft sources, such as the patellar and hamstring tendons. The AHPL tendon autograft offers a promising alternative with favorable anterior knee pain and minimal donor site morbidity.Conclusion: In ACL reconstruction, the AHPL tendon autograft demonstrates excellent outcomes regarding anterior knee pain, as measured by the Kujala score.Keywords: anterior cruciate ligament (ACL) reconstruction, anterior knee pain, peroneus longus tendon autograft, anterior half of the peroneus longus (AHPL), Kujala score